The Use of Artificial Intelligence in Education in the Age of Digitalization - Jumagulovich, Musagaliev, Ajiniyaz; Tansikbaevna, Jusupova, Anjim; Ivanovich, Gretchenko, Anatoly; Anatolievich, Gretchenko, Alexander (Journal of Ecohumanism, 2025)
The authors of the article consider the domestic experience of introducing new digital technologies using artificial intelligence (AI) at the Plekhanov Russian University of Economics from the point of view of a student, teacher, administrative and managerial staff. The development of neural network technologies, artificial intelligence technologies in the educational field, and human resource management in society determines and directs the vectors of training modern specialists who are able to resolve complex contradictions in the current system of social organization and respond to a number of challenges related to ethical and social aspects. The systematic emphasis on ensuring continuity in the educational process of a modern young specialist forms a set of his competencies capable of providing not only answering complex answers and questions in the labor market, but also shaping, developing the student's correct formulation of tasks and their solution.